Increasing Production of the Meatball Business Using an Automatic Meatball Machine - Mediaswanti, Kun Aussieanita; Asnah, Asnah; Widyastuti, Fikka Kartika; Anggraini, Sinar Perbawani Abrina (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Meatballs are very popular with everyone, from children to adults. In the process of printing meatballs into rounds, Meatball Wilujeng UMKM still uses it manually. Wilujeng meatballs are hand-made into meatball molds. In the molding process, it takes about 60 minutes to produce 9 kg of dough, which will form about 900 meatballs. The already-formed meatball is not uniform when hanging by a fist, and when picking up the dough with a spoon. This is the main problem in making meatballs. To overcome this, a tool was designed to automatically and efficiently make meatballs. So that this tool will ease and speed up the process of making meatballs for Wilujeng meatballs. The purpose of this service activity is to increase the meatball business's production by designing an energy-efficient, appropriately sized automatic meatball machine. The design of the meatball machine results in dimensions (D x W x H x H) of 25×15×70, a voltage of 15V, and a power of 370 W. It can produce 20 kg of dough in just 10 minutes, making 333 meatballs, resulting in a 122% increase using the % efficiency formula.